Case Report: Blinatumomab therapy for the treatment of B-cell acute lymphoblastic leukemia patients with central nervous system infiltration - Cao, Han-Yu; Chen, Hui; Liu, Song-Bai; Gong, Wen-Jie; Qian, Chong-Sheng; Zhang, Tong-Tong; Wan, Chao-Ling; Huang, Si-Man; Xu, Nan; Dai, Hai-Ping; Xue, Sheng-Li (Frontiers in Immunology, 2023)
The treatment of B-cell acute lymphoblastic leukemia (B-ALL) with central nervous system (CNS) involvement poses a significant clinical challenge because most chemotherapeutic agents exhibit weak permeability to the blood-brain barrier (BBB). In addition, current anti-CNS leukemia treatments often bring short or long-term complications. Immunotherapy including chimeric antigen T-cell therapy and bispecific antibody have shown profound treatment responses in relapsed/refractory B-ALL. However, there is a lack of data on the efficacy of bispecific antibody in treating B-ALL with CNS involvement. Here, we report two ALL patients with CNS leukemia who received blinatumomab. Case 1 was diagnosed with chronic myeloid leukemia in lymphoid blast phase. The patient developed CNS leukemia and bone marrow relapse during the treatment with dasatinib. Case 2 was diagnosed with B-ALL and suffered early hematologic relapse and cerebral parenchyma involvement. After treatment with one cycle of blinatumomab, both patients achieved complete remission in the bone marrow and CNS. Furthermore, this is the first report on the efficacy of blinatumomab in treating CNS leukemia with both of the cerebral spinal fluid and the cerebral parenchymal involvement. Our results suggest that blinatumomab might be a potential option for the treatment of CNS leukemia.